Synthesis and characterization of novel thermo- and salt-sensitive amphoteric terpolymers based on acrylamide derivatives - Ayazbayeva, A.Ye.; Shakhvorostov, A.V.; Seilkhanov, T.M.; Aseyev, V.O.; Kudaibergenov, S.E. (KU Publ., 2021)
A novel linear amphoteric terpolymers based on neutral monomer — N-isopropylacrylamide (NIPAM), anionic monomer — 2-acrylamido-2-methyl-1-propanesulfonic acid sodium salt (AMPS), and cationic monomer — (3-acrylamidopropyl) trimethylammonium chloride (APTAC) were synthesized by free-radical polymerization in aqueous solution and characterized by methods of 1H NMR and FTIR spectroscopy, TGA, GPC, Dynamic light scattering (DLS) and zeta-potential. The thermal and salt sensitivity of amphoteric ternary polymers of various compositions, particularly, [NIPAM]:[AMPS]:[APTAC] = 90:2.5:7.5; 90:5:5; 90:7.5:2.5 mol.% were studied in aqueous and aqueous-salt solutions in the temperature range from 25 to 60 C and at the NaCl ionic strength  interval from 10–3 to 1M. It was found that due to hydrophobic/ hydrophilic balance, the temperature dependent conformational and phase change of macromolecular chains becomes sensitive to salt addition and allows the fine-tuning of the phase transition. In aqueous and aqueous-salt solutions, the average hydrodynamic size of amphoteric terpolymers is varied from 8 to 300 nm exhibiting bimodal distribution at room temperature. The number average (Mn) and weight average (Mw) molecular weights, polydispersity index (PDI), and zeta-potentials of amphoteric terpolymers in aqueous solutions were determined.
Акриламид туындыларының негізінде алынған жаңа термо- және тұзға сезімтал амфотерлік терполимерлерді синтездеу және зерттеу
Синтез и исследование новых термо- и солечувствительных амфотерных терполимеров на основе производных акриламида
Keywords: amphoteric terpolymers; thermal response; salt sensitivity; phase transition temperature; hydrophobic/ hydrophilic balance; core-shell structure